2018
DOI: 10.1002/pon.4708
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to discontinuing breast cancer screening in older women: A qualitative study

Abstract: Among older women who planned to continue screening, intentions to continue breast cancer screening appear to be highly resilient and resistant to recommendations from physicians or expert/government panels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Nine of the included studies were quantitative, 14 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 8 were qualitative, 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 and 4 used mixed methods. 36 , 37 , 38 , 39 Ten studies examined breast cancer screening, 21 , 22 , 24 , 25 , 29 , 30 , 31 , 32 , 36 , 39 3 assessed cervical cancer, 26 , 28 , 34 1 assessed prostate cancer, 23 and 7 assessed some combination of breast, prostate, cervical, and colorectal cancer screening. 13 , 14 , 27 , 33 , 35 , 37 , 38 Thirteen studies included women only, 21 , 22 , 24 , 25 , 26 , 28 , 29 , 30 , 31 , 32 , 34 , 36 , 39 1 included men only, 23 and 7 included a combination of men and women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine of the included studies were quantitative, 14 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 8 were qualitative, 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 and 4 used mixed methods. 36 , 37 , 38 , 39 Ten studies examined breast cancer screening, 21 , 22 , 24 , 25 , 29 , 30 , 31 , 32 , 36 , 39 3 assessed cervical cancer, 26 , 28 , 34 1 assessed prostate cancer, 23 and 7 assessed some combination of breast, prostate, cervical, and colorectal cancer screening. 13 , 14 , 27 , 33 , 35 , 37 , 38 Thirteen studies included women only, 21 , 22 , 24 , 25 , 26 , 28 , 29 , 30 , 31 , 32 , 34 , 36 , 39 1 included men only, 23 and 7 included a combination of men and women.…”
Section: Resultsmentioning
confidence: 99%
“…34 Five studies analyzed factors associated with screening intention 21 , 22 , 24 , 26 or willingness to stop, 28 1 assessed decisions within a discrete choice experiment for a hypothetical patient, 14 and 1 examined factors associated with the decision process (eg, goals, concerns, and knowledge). 27 Two studies asked closed questions about screening, 23 , 25 9 asked open questions about screening 29 , 31 , 32 , 34 , 39 or specifically about stopping, 13 , 30 , 33 , 35 and 3 asked both open and closed questions. 36 , 37 , 38 See Table 1 for a summary of the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Patient attitudes and behaviors that contribute to that discomfort include anger and decreased trust with physicians who recommend screening cessation, and a desire for screening even if they would not undergo treatment for cancers identified. 20,24 These issues are reflected in our Theme 2 results, and highlight the need for a shared paradigm of screening between clinicians and patients. This may help ameliorate a key challenge to changing screening behavior: patients tend to overestimate the benefits and underestimate the potential harms of screening.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with the limited literature that showed that older adults are reluctant to stop cancer screening based on life expectancy. 10 , 20 For example, the study by Housten et al 20 found that impaired health status and shorter life expectancy did not stop patients from wanting to continue breast cancer screening. Our study delves deeper in the reasons behind the low impact of life expectancy on the decision to continue or stop cancer screening.…”
Section: Discussionmentioning
confidence: 99%